2005
DOI: 10.1161/01.res.0000175722.21555.55
|View full text |Cite
|
Sign up to set email alerts
|

Gene Transfer of Neuronal Nitric Oxide Synthase to Carotid Body Reverses Enhanced Chemoreceptor Function in Heart Failure Rabbits

Abstract: Abstract-Our previous studies showed that decreased nitric oxide (NO) production enhanced carotid body (CB) chemoreceptor activity in chronic heart failure (CHF) rabbits. In the present study, we investigated the effects of neuronal NO synthase (nNOS) gene transfer on CB chemoreceptor activity in CHF rabbits. The nNOS protein expression and NO production were suppressed in CBs (PϽ0.05) of CHF rabbits, but were increased 3 days after application of an adenovirus expressing nNOS (Ad.nNOS) to the CB. As a contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
101
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(112 citation statements)
references
References 46 publications
9
101
0
2
Order By: Relevance
“…A specific nNOS inhibitor (SMTC) totally abolished the effect of Ad.nNOS on the K ϩ current in the CB glomus cells from CHF rabbits and also reduced the K ϩ currents in the CB glomus cells from sham rabbits, regardless of gene transfer of Ad.nNOS. Our previous study has demonstrated that Ad.nNOS gene transfer to the CB reverses the enhanced CB chemoreceptor activity and peripheral chemoreflex sensitivity in CHF rabbits (Li et al 2005). These data suggest that the nNOS down-regulation in CB glomus cells reduces the outward K ϩ currents and contributes to the enhanced chemoreceptor activity in CHF rabbits.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…A specific nNOS inhibitor (SMTC) totally abolished the effect of Ad.nNOS on the K ϩ current in the CB glomus cells from CHF rabbits and also reduced the K ϩ currents in the CB glomus cells from sham rabbits, regardless of gene transfer of Ad.nNOS. Our previous study has demonstrated that Ad.nNOS gene transfer to the CB reverses the enhanced CB chemoreceptor activity and peripheral chemoreflex sensitivity in CHF rabbits (Li et al 2005). These data suggest that the nNOS down-regulation in CB glomus cells reduces the outward K ϩ currents and contributes to the enhanced chemoreceptor activity in CHF rabbits.…”
Section: Discussionmentioning
confidence: 83%
“…Although our studies have found that NO plays an important role in regulating K ϩ channels of glomus cells, chemoreceptor discharge, and chemoreflex sensitivity in sham and CHF rabbits (Ding et al 2008;Li et al 2004Li et al , 2005Sun et al 1999b), it is unclear whether NOS is present in the rabbit CB glomus cell. In rats and cats, NOS was found to exist in the extensive plexus of nerve fibers and vessels surrounding glomus cells, but not within glomus cells (Dvorakova and Kummer 2005;Wang et al 1993Wang et al , 1994.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…During this interval, unpaced left ventricular contractility and ejection fraction decline to levels equivalent to moderate compensated CHF in patients. 24,26,27 Single-unit discharge activity of CB chemoreceptors, both at rest and in response to hypoxia, is similarly enhanced over the same time course (Figure 2A). 25 This increased central input from the CB provides a tonic excitatory influence on sympathetic outflow, because hyperoxia reduces resting RSNA in CHF but not control animals ( Figure 2B).…”
mentioning
confidence: 72%
“…10 However, basal NO production and nNOS expression within the CB are depressed in CHF. 25,26 Thus, the tonic inhibitory effect of NO on the activity of CB chemoreceptors, demonstrated in the CB of normal rabbits, is virtually absent in CHF rabbits. 25 The marked down regulation of endogenous nNOS in the CB plays a major role in the enhanced CB chemoreceptor activity in CHF rabbits.…”
mentioning
confidence: 98%